Исследование взаимодействия ДНК с примесными белками - Ахрем, А.А.; Егорова, В.П.; Егоров, А.С.; Крот, В.И.; Ландо, Д.Ю.; Лука, З.А. (Биополимеры и клетка, 1989)
Исследовано взаимодействие ДНК, выделенной из селезенки коровы, с загрязняющими ее примесными белками. Показано, что последние не являются гистонами и их связи с ДНК разрушаются в присутствии мочевины, но сохраняются при высоких концентрациях Na⁺ . Примесные белки не изменяют термостабильности ДНК и распределены между макромолекулами неравномерно: менее 10 % ДНК содержат более 70 % всех белков. Досліджено взаємодію ДНК, виділеної з селезінки корови, із забруднюючими її домішковими білками. Показано, що останні не є гістонами і їхні зв’язки з ДНК руйнуються за присутності сечовини, але зберігаються за високих концентрацій Na⁺. Домішкові білки не змінюють термостабільності ДНК і розподілені між макромолекулами нерівномірно: менше 10 % ДНК містять більше 70 % усіх білків. DNA isolated from the bovine spleen has been investigated for its interaction with protein contaminants. It is shown that the contaminants are not histones and their binding is determined by the nonionic contacts which are destroyed in the presence of urea and retain with high concentrations of NaCl. The protein contaminants do not change thermostability of DNA and they are distributed irregularly among the macromolecules: less than 10 % of DNA contains more than 70 % of all the proteins.